O estabelecimento da filiação na reprodução humana assistida à luz dos direitos fundamentais e do direito civil brasileiro - Haab, Tuiskon Bejarano (2016)
The current work aims to study the establishment of the filial filial relationships arising from assisted human reproduction. To this end, the human reproductive issue is initially approached as a social circumstance, in light of the evolution of social circles. This analysis will allow the discovery of social rules applicable to artificial procreation and the resulting filiation. Next step, we move onto the study of reproductive self-determination development and its impact on the use of assisted human reproduction at the international and national levels. In the Brazilian scenario, it discusses the legal constraints and possibilities of such self-determination, especially in the constitutional context, pondering about its effects on the filial relationship stemmed from assisted reproduction. At last, we look into the filiation institution in the Brazilian legal system scenario, pointing out which of and how this institution´s fundamentals and assumptions can be used for determining the filiation in the artificial reproduction. We conclude it with proposals of establishing parent-child relationships in several hypotheses of artificial procreation.